A simple and practical model for reactive plumes. (1st January 2000) - Delamare, L.; Coppalle, A.; Gonzalez, M.
Pollutants emitted from industrial stacks can be transformed by chemical reactions. An interesting case is the NO to NO2 conversion due to reactions with the ambient ozone. A simple and practical model has been developed to calculate this conversion in the vicinity of the source. Spatial distributions of the reactive species concentrations in the plume are represented by generalised Gaussian profiles. The influence of non-linear chemistry is taken into account by means of different dispersion parameters for each species. The model itself consists of a limited number of ordinary differential equations which are easy to solve numerically. The wind tunnel reactive plume experiment of Builtjes has been simulated. Comparison between the results of this simple model and calculations involving the complete partial differential equations solved on a refined mesh shows that this generalised Gaussian representation of the transverse profiles is valid except very near the source. It turns out that the influence of chemistry on the dispersion parameters has to be taken into account in order to predict the NO/NO2 conversion accurately.